Faktor kejayaan kritikal dalam melaksanakan pelan induk operasi dan penyenggaraan aset tak alih - Md. Yunus, Norhidayah (2014)
Maintenance and Operation Blueprint for Iskandar Malaysia was established to ensure local authorities immovable asset maintenance management in line with Government Asset Management Policy 2009. However, Maintenance and Operation Blueprint for Iskandar Malaysia have not fully implemented by local authorities in the maintenance management of immovable asset. Therefore, the aim of this research is to provide detailed explanations about the critical success factors for Maintenance and Operation Blueprint implementation in the maintenance management of local authorities immovable asset so that the Maintenance and Operation Blueprint Plan for Iskandar Malaysia can be implemented successfully. Five local authorities in Iskandar Malaysia were the sample in this research which are Johor Bahru City Council, Johor Bahru Tengah Municipal Council, Kulai Municipal Council, Pasir Gudang Municipal Council and Pontian District Council. Twenty five respondents from ten executive level managers and fifteen operating unit managers had been chosen as respondents in this research. The data has been analysed qualitatively using critical success factors approach. Results of the analysis showed that the local authorities in Iskandar Malaysia do not fully implement the Maintenance and Operation Blueprint in the maintenance management of immovable asset because there are seven flaws that interfere with the successful implementation of the Maintenance and Operation Blueprint. There are seven critical success factors for the implementation of Maintenance and Operation Blueprint for Iskandar Malaysia in the maintenance management of local authorities immovable asset according to the local authority perspective which are effective approach, cooperation, effective resources, leadership, skills and abilities, commitment and beliefs. Research contribution to the body of knowledge is to produce a new approach for successful blueprint implementation. In conclusion, the critical success factors for implementation of Maintenance and Operation Blueprint Plan for Iskandar Malaysia in the maintenance management of local authorities immovable asset should be implemented so that the Maintenance and Operation Blueprint Plan for Iskandar Malaysia can be implemented successfully.